1999
DOI: 10.1046/j.1365-2362.1999.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma acylation stimulating protein, adipsin and lipids in non‐obese and obese populations

Abstract: The present data suggest involvement of the ASP/adipsin pathway in the pathogenesis of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
99
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 34 publications
(48 reference statements)
7
99
2
1
Order By: Relevance
“…However, in studies involving humans, adipsin was found to be higher with increased body mass. 22,23 The upregulation of adipsin gene expression during adipogenesis in this study correlates well with similar observation reported by other research groups. 15,24 PPARg is the most adipose specific of the PPAR subfamily of nuclear hormone receptors, and exists as two isoforms: PPARg 1 and PPARg 2 .…”
Section: Discussionsupporting
confidence: 92%
“…However, in studies involving humans, adipsin was found to be higher with increased body mass. 22,23 The upregulation of adipsin gene expression during adipogenesis in this study correlates well with similar observation reported by other research groups. 15,24 PPARg is the most adipose specific of the PPAR subfamily of nuclear hormone receptors, and exists as two isoforms: PPARg 1 and PPARg 2 .…”
Section: Discussionsupporting
confidence: 92%
“…In this sense, a previous study (Maslowska et al, 1999) explains these results through the ASP activity rising the glucose transport additively and independently of insulin mechanisms, and stimulating the diacylglycerol acyltransferase enzyme, involved in triacylglycerol synthesis pathway. In agreement with insulin concentrations, and in contrast to our results, positive correlation with circulating C3 has been described (Yudkin, 2000;Halkes et al, 2001;Ylitalo et al, 2001), highlighting its possible role as a predictor of risk to develop type 2 diabetes and related metabolic disorders (Engstrom et al, 2005b).…”
Section: Discussionmentioning
confidence: 77%
“…As ASP, a product derived from C3, rises the efficiency of synthesis of triacylglycerols in adipocytes, stimulating glucose absorption, activating the diacylglycerol acyltransferase (DGAT) and inhibiting the hormone-sensitive lipase (Sniderman et al, 2000) and high concentrations of C3 are able to increase circulating triacylglycerols (Maslowska et al, 1999), the C3/ASP system has been hypothesized as a modulator of the fatty acid metabolism in adipose tissue. On the other hand, C3 knockout mice do not respond to a high fat diet with ethanol, tending to reduce liver steatosis (Bykov et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, however, several studies have shown that ASP levels are high in obese subjects, possibly as a direct consequence of increased fat mass. 30,29,11,12 It was recently hypothesized that these high ASP levels represent an ASP-resistant state, whereas low ASP levels indicate increased sensitivity of adipose tissue towards ASP. 14 This hypothesis is supported by in vitro data.…”
Section: Discussionmentioning
confidence: 99%
“…10,29 In one subject, fasting ASP could not be determined post-training due to technical problems. For determination of FFA, glycerol, triglycerides and glucose, blood was collected in tubes containing 30 ml of 0.2 M EDTA.…”
Section: Asp and Endurance Training P Schrauwen Et Almentioning
confidence: 99%